World history (Guilford, Conn., 2005)
This informative anthology provides convenient, inexpensive access to a wide range of current, carefully selected articles from some of the most respected magazines, newspapers, and journals published today. Within the pages of this volume are interesting well-illustrated articles by historians, educators, researchers, and writers, providing an effective and useful perspective on world history from prehistory to 1500.
Keywords: World history,History, Ancient,Lịch sử Thế Giới,Lịch sử, cổ đại